Concise economic history of Britain; From the earliest times to 1750 - Clapham, Sir John (Cambridge, 1957)
This book, issued in 1951, a few slips and misprints were corrected, and alterations of sub stance were made on the following points: the Roman roads (p. 34); early fulling-mills on the Continent (p. 154); estimates of population in the eighteenth century (pp. 186 and 189). I also added note 2 on p. 156. Nearly all these alterations were based on work published after Sir John Clapham's death. In this third impression, besides correcting a few further slips, I have added note 4 on p. 27, since it is now clear that the Roman made more use of water-mills in Britain than Sir John Clapham believed. On pp. 154-5 I have revised his account of the numbers and distribution of early fulling-mills in Eng land in the light of recent discoveries; and on p. 158 I have deleted some figures derived from the unreliable ulnagers' accounts. Sir John Clapham also made use of the ulnagers' accounts in his description of the distribution of the cloth industry in the late fourteenth century on p. 191; but for the reason given in note I to this page I have allowed his words to stand. I have to thank Professor E. M. Carus-Wilson, Professor T. S. Ashton, Professor D. V. Glass and Dr G. H. S. Bushnell for help in making these corrections.
Keywords: Economic history